Model Predictive Control-based supervisor for primary support of grid-interactive microgrids. (May 2023) - Legry, Martin; Dieulot, Jean-Yves; Colas, Frédéric; Bakri, Reda
Abstract: Networked microgrids is a cluster of local grids that can be connected through a weak network and can provide ancillary services. On a system point of view, it is desirable that every microgrid exhibits a behaviour at the Point of Common Coupling (PCC) which enables to share active and reactive powers with other grids. This paper proposes a Model Predictive Supervisor that encompasses internal objectives and enforces a virtual droop control at the PCC. The supervisor uses a prediction module based on a model of the microgrid and an outer loop which supplies the PCC powers with respect to the aggregated capability diagram at the PCC. For a weak network, this diagram depends on the PCC voltage that varies with time, generating a set of time varying non-linear constraints. The supervisor generates the references to control the local distributed generators which are inside the microgrid. Through the three steps developed in this paper, the need for model based control is highlighted and a Model Predictive based Controller proposed and validated from simulations.